Magnetic resonance imaging in isolated sagittal synostosis - Engel, Michael; Hoffmann, Jürgen; Mühling, Joachim; Castrillón-Oberndorfer, Gregor; Seeberger, Robin; Freudlsperger, Christian (The journal of craniofacial surgery, 2012)
Isolated fusion of the sagittal suture is the most prevalent form of craniosynostosis. Although the typical clinical appearance usually points the way to the right diagnosis, computed tomographic (CT) scans are still recommended as necessary tools for both the diagnosis of scaphocephaly and the preoperative planning. Because CT scans are accompanied by the biological effects of ionizing radiation, some authors have already postulated the use of magnetic resonance imaging (MRI) especially because MRI seems to be valuable for detecting intracranial anomalies compared with CT scans. Hence, we investigated the preoperative MRIs of 42 children with isolated sagittal synostosis to evaluate the frequency of brain anomalies and their therapeutic consequences. In our study, 10 patients (23.8%) showed pathologic MRI findings such as ventricular dilatation and hypoplastic corpus callosum, whereas 32 patients (76.2%) had an unremarkable MRI except a pathognomonic secondary deformation of the brain caused by the abnormally shaped skull, which was present in all patients. Seven patients showed clinically significant symptoms including papilledema or psychomotoric developmental delay; however, the clinical appearance was not predictive for pathologic MRI findings and vice versa. As the detection of brain anomalies had no influence on the surgical procedure or led to any additive therapy in our patients, we conclude that evaluation of possible pathologic brain findings does not legitimate the general use of MRI in clinically normal children with isolated sagittal synostosis.